1257 IMPROVING HYDRATION IN ELDERLY PATIENTS ON OUTLIER WARDS AT NEWHAM UNIVERSITY HOSPITAL (NUH). (16th January 2023) - Smith, C R E D; Aziz, S; Duper, S V
Abstract: Introduction: Dehydration is a major contributing factor to morbidity and mortality in elderly patients, as they are at greater risk and more vulnerable to the consequences of inadequate fluid intake. Care of the Elderly (COE) wards are set up to meet the specific care needs of elderly patients, however, these care needs are not consistently met on medical outlier wards at NUH. This project aimed to improve hydration-related patient care on outlier wards using a sustainable intervention by increasing average daily fluid intake (ADFI) by 50% and patients with drinks within an arm's reach by 50%. Methods: Cycle 1 : Hydration parameters (ADFI, glasses within reach, drinks offered, glasses filled) were audited for patients on two COE wards (n=25) and four outlier wards (n=19). Cycle 2: Reminder to offer patients a drink added to outlier patients' ward round entries and nurses verbally informed over 1 week (n=14). Cycle 3: 'Think Drink' poster placed at outlier patients' bedsides as a visual reminder and nurses verbally informed over 1 week (n=15). Results: Cycle 1: ADFI was 774mls greater on COE than outlier wards, 299% more glasses within reach, 62% more drinks offered, 78% more glasses filled. Cycle 2: 52% increase in ADFI (258mls), 104% more drinks within reach, 11% more drinks offered; 15% less glasses filled. Cycle 3: further 8% increase in ADFI (62mls), 87% more glasses within reach, 4% more drinks offered, and 124% more glasses filled. Overall: 65% increase in ADFI, 280% more glasses within reach, 15% more drinks offered, and 90% more filled glasses. Conclusions: An important gap in care was identified between COE and outlier wards, leaving elderly outlier patients vulnerable to dehydration. 'Think Drink' poster acted as a successful visual reminder for staff and visitors demonstrated by an increase in all hydration parameters, improving hydration-related patient care.